NRM-Mammals - Daniela C Kalthoff (Swedish Museum of Natural History, 2010)
This database contains information on the specimens that have been registered so far in the mammal collection of the Swedish Museum of Natural History. This dataset is based on extensive collections of mammals housed at the Swedish Museum of Natural History, having approximately 120,000 objects, mainly in the form of skeletons and skins, but also alcohol-preserved animals and tissue samples. Some of the specimens are mounted and displayed in museum exhibitions, the collection is, however, primarily used in research and for educational purposes.

The collections include 18th century, even late 17th century, specimens covering a little more than 40% of the world's known mammals. The data set, and the collections it reflects, has a focus on Swedish and European species as well as substantial representation of South American, African, and Southeast Asian faunas. The mammals that are part of the state-owned wildlife ("statens vilt") are particularly well represented.
Keywords: Occurrence; Observation; Occurrence; OCCURRENCE; Biological Sciences; Biologi